Control of Vertex Geometry, Structure Dimensionality, Functionality, and Pore Metrics in the Reticular Synthesis of Crystalline Metal—Organic Frameworks and Polyhedra. - Furukawa, Hiroyasu; Jaheon Kim; Ockwig, Nathan W.; O'keeffe, Michael; Yaghi, Omar M. (Journal of the American Chemical Society, 2008)
Metal-organic polyhedra and frameworks (MOPs and MOFs) were prepared by linking square units M(CO) (M = Cu and Zn) with a variety of organic linkers designed to control the dimensionality (periodicity) and topology of the resulting structures. We describe the preparation, characterization, and crystal structures of 5 new MOPs and 11 new MOFs (termed MOP-14, -15, -17, -23, -24 and MOF-114, -115,-116,-117,-118,-119,-222,-601,-602,-603,-604)and show how their structures are related to the shape and functionality of the building blocks. The gas uptake behaviors of MOP-23 and MOF-601 to -603 are also presented as evidence that these structures have permanent porosity and rigid architectures.